Time-dependent Hartree-Fock approach to nuclear "pasta" at finite temperature - Schuetrumpf, Bastian; Klatt, Michael; Iida, K.; Maruhn, J. A.; Mecke, Klaus; Reinhard, Paul-Gerhard (Physical Review C - Nuclear Physics, 2013)
We present simulations of neutron-rich matter at subnuclear densities, like supernova matter, with the time-dependent Hartree-Fock approximation at temperatures of several MeV. The initial state consists of alpha particles randomly distributed in space that have aMaxwell-Boltzmann distribution in momentum space. Adding a neutron background initialized with Fermi distributed plane waves the calculations reflect a reasonable approximation of astrophysical matter. This matter evolves into spherical, rod-like, and slab-like shapes and mixtures thereof. The simulations employ a full Skyrme interaction in a periodic three-dimensional grid. By an improved morphological analysis based on Minkowski functionals, all eight pasta shapes can be uniquely identified by the sign of only two valuations, namely the Euler characteristic and the integral mean curvature. In addition, we propose the variance in the cell density distribution as a measure to distinguish pasta matter from uniform matter.